Partnering with Native Communities to Develop a Culturally Grounded Intervention for Substance Use Disorder. Issue 1 (10th July 2019) - Skewes, Monica C.; Hallum‐Montes, Rachel; Gardner, Scott A.; Blume, Arthur W.; Ricker, Adriann; FireMoon, Paula
Abstract: Studies have documented serious disparities in drug and alcohol‐related morbidity and mortality among American Indians and Alaska Natives (AI/ANs) compared to other ethnic groups in the U.S. despite high rates of abstinence in these groups. Further complicating these health disparities are barriers to accessing evidence‐based treatments that are culturally appropriate and acceptable. As part of a research program to promote health equity in rural communities, we developed an academic‐community partnership to create a culturally grounded intervention for adults with substance use disorder (SUD) residing on a rural AI reservation. We describe the early phases of our long‐term Community Based Participatory Research project and report findings from the first study we conducted. This key informant interview study consisted of in‐depth qualitative interviews with 25 tribal members knowledgeable about substance use and recovery on the reservation. The goal was to understand social norms and cultural conceptualizations of substance use to inform the development of a sustainable, community‐driven intervention. Participants reported that a holistic approach to recovery that emphasizes spiritual, cultural, and interpersonal harmony and connectedness was important to the community and would be necessary for the intervention to succeed. They also emphasized the need for a multi‐level intervention targeting individuals, families, and the community as a whole. Through this initial study, we not only gained valuable information that will be used to guide future research and treatment efforts, but we also strengthened our partnership and built trust with the community. In this manuscript we tell the story of the development of our project and describe our shared vision for future directions. Highlights: Our academic‐community partnership was formed to address health disparities in rural Montana. We conducted in‐depth interviews with key informants from a rural American Indian reservation. Participants desired a holistic, multi‐level intervention that involves culture and spirituality. Next, we will culturally adapt relapse prevention for American Indians with substance use disorder.